Challenging the power invested in the International English Language Testing System (IELTS): Why determining ‘English’ preparedness needs to be undertaken within the subject context - Pilcher, Nick; Richards, Kendall (Power and education, 2017)
Higher education institutions worldwide base international student recruitment on the assumption that their preparedness in ‘English’ is assured if they reach a certain level in tests such as the International English Language Testing System (IELTS). This assumes an abstract, objectivist view of language that sees the ‘English’ as removable for testing in any context. However, in an individual, subjectivist view of language, ‘English’ is inextricably linked with context – that is, subject content which symbiotically connects thought and meaning. In this article, the authors outline these views of language and consider the ‘English’ of IELTS. They then detail interviews and focus groups which they conducted with lecturers in the subject areas of Design, Nursing, Engineering, Business, Computing and Psychology. These researched the ‘English’ required in subjects and the thinking underpinning it. The authors go on to present and discuss results around three themes of ‘How “English” is specific to the content of subjects’, ‘How the “English” of subjects is underpinned by unique ideological and psychological elements’ and ‘How the non-textual elements of different subjects are intertwined with their “English”’. The results illustrate why it is necessary to challenge the power invested in IELTS, and why determining English preparedness needs to be undertaken within the subject context.